Pandemic-Related Challenges and Organizational Support Among Personnel in Canada's Defense Establishment - Goldenberg, Irina; Denomme, William James; Lee, Jennifer E. C. (Frontiers in Public Health, 2022)
In the final week of March 2020, 2.8 million Canadians were away from their usual places of work and engaging in remote and/or telework to mitigate the spread of COVID-19 (Statistics Canada, 2020). Similarly, most members of the Department of National Defence (DND) and Canadian Armed Forces, including members of the regular force (Reg F), the primary reserve force (P Res), and the DND public service (DND PS), were working from home. The COVID-19 Defence Team Survey was administered to gain insight into work, health, and family-related challenges members have faced due to these new work arrangements amid the pandemic. Respondents’ most common work-related challenges included dissatisfaction with technology/software, work arrangements, ergonomics, work-life balance, communication within the organization, and the uncertainties regarding career development. The most common personal or family-related challenges included social isolation, the impact of the pandemic on mental health, school closures and homeschooling, caring for vulnerable family members, and childcare concerns. The most common stress-management and coping strategies included exercise, spending time outdoors, communicating or spending time with family members, household chores/projects, mind-body wellness exercises, and playing games. The most common recommendations made by respondents to improve their work- or personal-related situations included improving technological capabilities, streamlining communication, providing hardware and software necessary to ensure comfortable ergonomics, the provision of flexibility in terms of telework schedules, return-to-work decisions, and the expansion of benefits and access to childcare services. In terms of differences among the components, DND PS personnel were most likely to report dissatisfaction with technological changes and ergonomics, and to recommend improving these technological limitations to maximize productivity. Reg F members, on the other hand, were most likely to recommend increased support and access to childcare, and both Reg F and P Res members were more likely to mention that increased benefits and entitlements in response to the COVID-19 pandemic would be ameliorative. The results of this study highlight several important facts about the impact of the COVID-19 pandemic on personnel working in large, diverse organizations.